Toward best-effort services over WDM networks with fair access and minimum bandwidth guarantee. - Kam, A.C (IEEE Journal on selected areas in communications)
Most existing wavelength-division multiplexed (WDM) networks employ circuit switching, typically with one session having exclusive use of one entire wavelength. Consequently, they are not suitable for data applications involving bursty traffic patterns. The All-Optical Network (AON) Consortium has developed an all-optical LAN/MAN test bed which provides time-slotted WDM service. We explore extensions of this service to achieve fine-grained statistical multiplexing with different virtual circuits time sharing the wavelengths in a fair manner. We develop a very fast, best effort time-slotted WDM network protocol with very good fairness and throughput characteristics. As an additional design feature, our protocol supports the assignment of guaranteed bandwidths (GBW) to selected sessions. This feature acts as a first step toward supporting integrated services at the optical layer in WDM networks